2017
DOI: 10.4103/jcecho.jcecho_46_16
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular outflow tract thrombus in a child with dilated cardiomyopathy: An atypical location

Abstract: Dilated cardiomyopathy (DCM) may be associated with formation of intracardiac thrombi which may embolize and result in life-threatening complications. We present a 19-month-old female child with DCM who presented with a right hemispheric cerebrovascular accident. Urgent echocardiography revealed poor left ventricular systolic function and a thrombus attached to the interventricular septum along the left ventricular outflow tract. There was resolution of the thrombus following the use of warfarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Dilated cardiomyopathy (DCM) is characterized by LV dilation and systolic dysfunction as identified in this patient. Several studies revealed that intracardiac thrombi could be a complication of DCM [ 19 , 20 ]. Factors implicated in the formation of thrombi in DCM include low-velocity swirling of blood, abnormal endocardial surfaces, atrial fibrillation, and a hypercoagulable state [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dilated cardiomyopathy (DCM) is characterized by LV dilation and systolic dysfunction as identified in this patient. Several studies revealed that intracardiac thrombi could be a complication of DCM [ 19 , 20 ]. Factors implicated in the formation of thrombi in DCM include low-velocity swirling of blood, abnormal endocardial surfaces, atrial fibrillation, and a hypercoagulable state [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe malnutrition is common in developing countries and data indicates that malnourished children are at higher risk of dying once infected [ 6 ]. Additionally, dilated cardiomyopathy (DCM) is a phenotype of cardiomyopathy caused by idiopathic, familial, genetic mutations (primary) and inflammatory, congenital heart disease, oncologic, toxin-mediated, systemic, and nutritional disorders including protein-energy malnutrition (secondary) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%